2020
DOI: 10.1007/s12155-020-10135-6
|View full text |Cite
|
Sign up to set email alerts
|

A Performance Comparison of Low-Cost Near-Infrared (NIR) Spectrometers to a Conventional Laboratory Spectrometer for Rapid Biomass Compositional Analysis

Abstract: The performance of a conventional laboratory near-infrared (NIR) spectrometer and two NIR spectrometer prototypes (a Texas Instruments NIRSCAN Nano evaluation model (EVM) and an InnoSpectra NIR-M-R2 spectrometer) are compared by collecting reflectance spectra of 270 well-characterized herbaceous biomass samples, building calibration models using the partial least squares (PLS-2) algorithm to predict five constituents of the samples from the reflectance spectra, and comparing the resulting model statistics. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Further work at NREL demonstrated a large variation in the cell wall composition of corn stover from various harvests as predicted by NIRS (Templeton et al, 2009). Lately, the same group has demonstrated that potentially lowcost and portable spectrometers with limited spectral range provide predictions that are nearly as accurate as those of welldeveloped laboratory instruments (Wolfrum et al, 2020). Here, we demonstrate that a comparable "off the shelf" instrument is adequate to predict not only composition, but further extend the predictive capability to anatomical tissue type.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Further work at NREL demonstrated a large variation in the cell wall composition of corn stover from various harvests as predicted by NIRS (Templeton et al, 2009). Lately, the same group has demonstrated that potentially lowcost and portable spectrometers with limited spectral range provide predictions that are nearly as accurate as those of welldeveloped laboratory instruments (Wolfrum et al, 2020). Here, we demonstrate that a comparable "off the shelf" instrument is adequate to predict not only composition, but further extend the predictive capability to anatomical tissue type.…”
Section: Introductionmentioning
confidence: 52%
“…NIR spectra were collected on a Foss InfraXact 7,500 non-contact spectrometer over wavelengths from 570 to 1850 nm in reflectance with the empty cup (air) serving as a baseline. This is a reduced wavelength range compared to many studies using NIR for chemical composition prediction (typically covering the full NIR range from 800 to 2500 nm), but recent work has confirmed little reduction in model predictive capability when using reduced spectral range (Wolfrum et al, 2020). For correlation of chemical composition (i.e.…”
Section: Spectra Acquisitionmentioning
confidence: 99%
“…A diffuse reflectance detector, set to 17.25 mm spot size, scanned the samples at a wavelength of 400–2499.5 nm with 0.5 nm resolution. The dataset was evaluated using a previously developed NIRS composition model based on various biomass types (Templeton et al., 2016; Wolfrum et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Yan and Siesler [ 11 ] demonstrated the use of these low-cost FT-NIR, linear variable filters (LVFs), and diffraction NIR systems for both classification and measurement. Wolfrum et al [ 12 ] compared the performance of low-cost NIRS to a conventional laboratory spectrometer. In Section 3 , spectroscopy architectures are introduced, especially the Texas Instruments Digital Light Processing (DLP) technology for spectroscopy that has been used in this work [ 13 ].…”
Section: Introductionmentioning
confidence: 99%